Key elements and theoretical logic of application of PIC/S standards in improving drug GMP inspections in China: an analysis based on grounded theory - Hu, Di; Liao, Ping; Chen, Yuwen (Frontiers in Pharmacology, 2025)
ObjectiveCurrently, China regulatory authorities are committed to improving drug inspection by learning from international advanced experiences, such as the Pharmaceutical Inspection Co-operation Scheme (PIC/S), to boost the development of the pharmaceutical industry. In the past, there has been a lack of systematic discussion and comprehensive theoretical construction of the key elements affecting the improvement of China’s Good Manufacturing Practice (GMP) inspection. Through this study, the key elements and theoretical logic for applying PIC/S standards to improve China’s pharmaceutical GMP inspection work are constructed.MethodsThis study uses diverse data and applies grounded theory to construct a model, systematically presenting the key elements and theoretical logic of applying PIC/S standards in improving GMP inspections in China.ResultsThe study found that international recognized GMP regulations are external contextual elements, while internal driving elements include professionalization and specialization of inspectors, standardized inspection procedures, and maintain consistent quality levels. The internal dimensions of these four elements are independent, but they can not only individually influence but also partially overlap and have a combined impact Moreover, professionalization and specialization of inspectors, standardized inspection procedures, and maintain consistent quality levels have a dynamic, cyclical promoting effect on the application of PIC/S standards.ConclusionBased on China’s national conditions, this study deepens the theoretical framework and content of applying PIC/S standards to improve drug GMP inspections, providing a reference for public sectors to enhance the effectiveness of pharmaceutical regulation.